Effect of Gold Nanoparticles on the Photocatalytic and Photoelectrochemical Performance of Au Modified BiVO4 - Long, Mingce; Jiang, Jingjing; Li, Yan; Cao, Ruqiong; Zhang, Liying; Cai, Weimin (Nano-Micro Letters, 2011)
An efficient visible light driven photocatalyst, gold nanoparticles (NPs) modified BiVO4 (Au/BiVO4), has been synthesized by deposition-precipitation with urea method. Au/BiVO4 exhibits enhanced photocatalytic activity for phenol degradation under λ>400 nm irradiation but negligible activity under λ>535 nm, indicating that the surface plasmon resonance (SPR) effect is too weak for organic photodegradation. According to the photoelectrochemical results of the porous powder electrodes of BiVO4 and Au/BiVO4, the SPR effect of Au NPs has been assessed. The role of Au NPs as electron sinks or sources, which is controllable by incident photon energy and applied potentials, has been discussed.